PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY PADA MATERI SISTEM PERNAFASAN - Sadewa, Arya Yudha; Zakarijah, Masduki (Journal of Information Technology and Education (JITED), 2024)
The use of smartphones as a learning medium is still minimal. Thus, there is a big opportunity to use smartphones as an interactive learning medium. This research aims to; (1) Produce interactive learning media that is suitable for use in respiratory system material; (2) Providing practical learning media. This research is in the form of Research & Development (R&D) with the Multimedia Development Life Cycle (MDLC) development model with the stages of conceptualizing, designing, collecting materials, manufacturing, testing and distribution. The feasibility testing instrument is in the form of a questionnaire filled out by technical experts and students as final consumers. For testing, the instrument validity test was carried out using the product moment correlation technique, while the instrument reliability test was carried out using the Cronbach alpha technique. The result of this research is interactive learning media in the form of an Android application titled Kinerfa, which utilizes augmented reality technology. After alpha testing, the product was tested by students at SMP Negeri 1 Banjarnegara. The final test results show the product feasibility level with a percentage of 68.5% so that the product can be declared "feasible".